Acquisition of growth-inhibitory antibodies against blood-stage Plasmodium falciparum. - McCallum, F; Persson, K; Mugyenyi, C; Fowkes, F; Simpson, J; Richards, J; Williams, T; Marsh, K; Beeson, J (2008)
BACKGROUND: Antibodies that inhibit the growth of blood-stage Plasmodium falciparum may play an important role in acquired and vaccine-induced immunity in humans. However, the acquisition and activity of these antibodies is not well understood. METHODS: We tested dialysed serum and purified immunoglobulins from Kenyan children and adults for inhibition of P. falciparum blood-stage growth in vitro using different parasite lines. Serum antibodies were measured by ELISA to blood-stage parasite antigens, extracted from P. falciparum schizonts, and to recombinant merozoite surface protein 1 (42 kDa C-terminal fragment, MSP1-42). RESULTS: Antibodies to blood-stage antigens present in schizont protein extract and to recombinant MSP1-42 significantly increased with age and were highly correlated. In contrast, growth-inhibitory activity was not strongly associated with age and tended to decline marginally with increasing age and exposure, with young children demonstrating the highest inhibitory activity. Comparison of growth-inhibitory activity among samples collected from the same population at different time points suggested that malaria transmission intensity influenced the level of growth-inhibitory antibodies. Antibodies to recombinant MSP1-42 were not associated with growth inhibition and high immunoglobulin G levels were poorly predictive of inhibitory activity. The level of inhibitory activity against different isolates varied. CONCLUSIONS: Children can acquire growth-inhibitory antibodies at a young age, but once they are acquired they do not appear to be boosted by on-going exposure. Inhibitory antibodies may play a role in protection from early childhood malaria.